Introducción a la Hacienda - Del Vecchio, Gustavo (1955)
It is a guide to the first part of his book on "Introduzione alla Finanza", in which the author infers that finances could not be understood without a through knowledge of Economics, this one determining the laws which govern finances. To arrive at this conclusion, he surveys all the ancient and modern theories of finances, which he refutes one by one, after demonstrating their incompatibility with the economic phenomena. He concludes that the science of finances consists in the application of economic theory to the financial facts and that it is itself a part of the economic theory.